Freud's monotheism - Parsons, William Barclay 1955- (Cambridge elements, 2023)
This Element consists of three interrelated parts. 'What Freud Said' summarizes the salient details of Freud's psychology of religion: his views on the origins and development of western religions; on contemporary western monotheisms; on the 'unpsychological' proceedings of the religio-cultural super-ego; his qualified endorsement of religious forms of psychotherapy; and his cursory analysis of eastern religions.'What Freud got Wrong' surveys the history of the multidisciplinary critiques (anthropological, sociological, later psychoanalytic, theological/philosophical) that have been levelled at his interpretative strategies. 'Towards a Revised Psychoanalytic Theory of Religion' suggests that the best way forward is to employ a psychoanalytic theory of religion which, taking its cue from the history of its critique, houses reflective, inclusive and dialogical elements. It presents illustrations taken from a variety of contemporary religio-cultural phenomena (marvel movies; issues concerning religion, sexuality and gender; the Megachurch; QAnon) as portable lessons for such applications